The Rabbis' King-Parables : Midrash From the Third-Century Roman Empire - Appelbaum, Alan (Judaism in Context, 2010)
The Rabbis' King-Parables: Midrash From the Third-Century Roman Empire examines the ancient Rabbis at work using parables about kings; parables that reflect the Rabbis' ideas about the role of the ruler in society, and the relationship of humanity to God. It considers the parables as resistance literature in light of the work of theorists of dominated groups. It is the first systematic attempt to read the parables as sources for Roman history in over 100 years.